Polarised narratives and complex realities in Tanzania's Southern Agricultural Growth Corridor. Issue 4 (19th May 2017) - West, Jennifer; Haug, Ruth
ABSTRACT: This article assesses the controversy surrounding a high-profile agricultural investment initiative, the Southern Agricultural Growth Corridor of Tanzania (SAGCOT), which aims to modernise, commercialise, and transform Tanzania's agricultural sector. Drawing on a review of SAGCOT literature and findings from consultations with SAGCOT stakeholders and intended beneficiaries, the article outlines the polarised narratives of "opportunity" and "risk" informing SAGCOT debates, and presents research findings that challenge these narratives. The findings suggest that agricultural investments are rarely as glamorous or as gloomy in practice as the polarised narratives around SAGCOT suggest, and illustrate the challenges involved in directing agricultural investments in ways that balance multiple interests and objectives in practice.